2013
DOI: 10.1007/s00104-012-2392-9
|View full text |Cite
|
Sign up to set email alerts
|

Anastomosentechniken am GastrointestinaItrakt

Abstract: The correct suture technique for anastomoses of the gastrointestinal (GI) tract is a major task in the daily practice of surgery and a basic requirement for a successful operation. This article provides an overview of the surgical principles and techniques involved in the creation of intestinal anastomoses, including the differentiated use of various suturing aids in the GI tract. Hand sewn and stapled anastomotic techniques are illustrated and discussed. The ongoing discussion and question as to which techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…Shortening the operation time means reducing surgical trauma and intra-operative blood loss and also abating local infection and reducing the chance of surgical complications. However, the superiority of stapling did not extend to postoperative hospital stay, which is consistent with the previous reports that postoperative hospital stay time showed no difference between the patients who received stapler suturing and manual procedure after gastrectomy [9,11]. However, another study showed that stapling anastomosis shortens postoperative hospital stay in the patients with stomach and esophageal tumors [12].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Shortening the operation time means reducing surgical trauma and intra-operative blood loss and also abating local infection and reducing the chance of surgical complications. However, the superiority of stapling did not extend to postoperative hospital stay, which is consistent with the previous reports that postoperative hospital stay time showed no difference between the patients who received stapler suturing and manual procedure after gastrectomy [9,11]. However, another study showed that stapling anastomosis shortens postoperative hospital stay in the patients with stomach and esophageal tumors [12].…”
Section: Discussionsupporting
confidence: 88%
“…An ideal anastomosis should fulfill the following criteria: it must be well vascularized, safe, tension-free and spillage from the operation field should be avoided [8]. The manual procedure has been used in tract anastomosis for a long time, but stapler suturing has been increasingly used as an anastomotic method in digestive tract surgery in the past few years [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Anastomotic healing remains a significant challenge for all surgeons of the gastrointestinal tract, with a high impact on patient outcomes. Despite improvements in the management of nutritional status (29), pre-and postoperative glycemic control (30), tension-free anastomotic techniques (31), and a revered number of other related to anastomosis healing variables, the leakage rate still ranges from 2% to 7%, even when performed by experienced surgeons (1)(2)(3)32). Several animal studies have provided crucial information on a variety of anastomosis techniques; however, a systematic review on the subject revealed that the actual translational value to clinical practice seems to be very limited (33).…”
Section: Discussionmentioning
confidence: 99%
“…Anastomosis is generally performed for the surgery treating these three types of GI tract tumor. An ideal anastomosis should fulfill the following criteria: it must be well vascularized, safe, tension-free and spillage from the operation field should be avoided [ 8 ]. The manual procedure has been used in tract anastomosis for a long time, but stapler suturing has been increasingly used as an anastomotic method in digestive tract surgery in the past few years [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%